2020
DOI: 10.1002/jbm.b.34631
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the formation, adipogenic maturation, and retention of human adipose‐derived stem cell spheroids in scaffold‐free culture techniques

Abstract: While three‐dimensional spheroids outperform traditional two‐dimensional monolayer culture for human adipose‐derived stem cells (hASCs), there is not a consensus on the most successful method for enhancing their adipogenic differentiation and minimizing the loss of physiologically relevant, fatty spheroids during culture. To this end, we compared three culture methods, namely, elastin‐like polypeptide‐polyethyleneimine (ELP‐PEI) coated surfaces, ultra‐low attachment static culture, and suspension culture for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In addition to the scaffold mechanical properties, chemical composition of the scaffold materials and the porosity of the scaffolds also affect the adipogenic differentiation of hASCs. We and others have previously shown that changing the surface amine content can affect the size of the hASC spheroids, the stability of the spheroids over the culture period, and their differentiation capability [ 28 , 29 , 30 ]. While the chemistry experienced by the hASCs in the present study is different for the collagen-only (2C and 6C) scaffolds, the ELP containing (2C+E and 2C+E_c) scaffolds, and the crosslinked (2C_c, 2C+E_c, and 6C_c) scaffolds, our scaffold formation process did not introduce any additional amine groups into our scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the scaffold mechanical properties, chemical composition of the scaffold materials and the porosity of the scaffolds also affect the adipogenic differentiation of hASCs. We and others have previously shown that changing the surface amine content can affect the size of the hASC spheroids, the stability of the spheroids over the culture period, and their differentiation capability [ 28 , 29 , 30 ]. While the chemistry experienced by the hASCs in the present study is different for the collagen-only (2C and 6C) scaffolds, the ELP containing (2C+E and 2C+E_c) scaffolds, and the crosslinked (2C_c, 2C+E_c, and 6C_c) scaffolds, our scaffold formation process did not introduce any additional amine groups into our scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hydrogel scaffold chemistry, structure (e.g., porosity), and properties (e.g., modulus) on the ultimate function of the encapsulated cells remains an active area of research. Presence of positively charged amine groups have been shown to induce hASC spheroid formation, which led to an enhanced differentiation along adipogenic and osteogenic lineages [ 28 , 29 , 30 ]. Porosity and pore size also play an important role in supporting adipogenic differentiation of hASCs [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, none of the screened articles exclusively studied 2D culture; therefore, all articles included in this analysis report 3D culture methods. Data and analysis hereafter exclusively refer to the 27 articles [4,5,[8][9][10][11][12][13][15][16][17][19][20][21][22][23][24][25][26]28,30,31,33,38,44,45,48] identified to be most relevant to the central goal of this systematic review. Out of the 27 relevant articles, 26 articles used adipogenic medium to differentiate hASC into adipocytes in vitro.…”
Section: Differentiation Pathwaysmentioning
confidence: 99%
“…Gelatin was identified as one of the most commonly used scaffold materials as it naturally contains RGD peptides found in many ECM components that promote cell adhesion [13,16,17,21]. Collagen is another commonly used scaffold material as it is the most abundant protein in human adipose tissue ECM and, therefore, closely recapitulates the native tissue environment [10,31]. hASC attachment and adipocyte maturation have been shown to impact scaffold structure [10,16].…”
Section: Scaffold Culturementioning
confidence: 99%
See 1 more Smart Citation